Education and social mobility in a group of retirees of the Federal Commission of Electricity - Navarro Leal, Marco Aurelio (Universidad Autónoma de Tamaulipas, 2019)
This research had as an objective to look for evidence on the relations between education and ascendant social mobility in the Federal Commission of Electricity. The subjects of the study were a group of 83 retirees of this company who live in the metropolitan area of Tampico-Madero-Altamira. After a review of the theories that focus this theme, a cross, ex post facto method was designed, to ask them for information about two moments of their working life in the company. The analysis allowed for finding evidence about intra-generational labor mobility, but not for inter-generational mobility. On these results there were no differences on social mobility between men and women. The separation of job positions administered by the company and job positions administered by the union, allowed to observe that this intermediation imposes limits to social mobility of employees, which is an aspect that brings discussion on the limits of interpretations of Human Capital theory that do not take into account external variables to the education of individuals.